2005
DOI: 10.1158/1078-0432.ccr-04-1781
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Gemcitabine and Its Metabolizing Enzymes in Neuroblastoma

Abstract: Purpose: We examined the activity of gemcitabine against neuroblastoma in vitro and in vivo. In addition, we investigated the cellular mechanisms of high sensitivity to the agent in neuroblastoma cells. Experimental Design: We examined 11 neuroblastoma cell lines for sensitivity to gemcitabine and other chemotherapeutic agents used clinically for neuroblastoma. The in vivo sensitivity of neuroblastoma to gemcitabine was determined in xenograft models. Furthermore, the major metabolic enzymes of gemcitabine wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…The best synergy was found between AZD7762 and gemcitabine, as observed in other tumor systems. 4,5 Although gemcitabine is not yet a standard agent for the treatment of neuroblastoma, 31 our data strongly support the potential of combination therapy with checkpoint kinase inhibitor like AZD7762 and gemcitabine for recurrent tumors and for preventing the emergence of resistant clones.…”
Section: Discussionsupporting
confidence: 62%
“…The best synergy was found between AZD7762 and gemcitabine, as observed in other tumor systems. 4,5 Although gemcitabine is not yet a standard agent for the treatment of neuroblastoma, 31 our data strongly support the potential of combination therapy with checkpoint kinase inhibitor like AZD7762 and gemcitabine for recurrent tumors and for preventing the emergence of resistant clones.…”
Section: Discussionsupporting
confidence: 62%
“…Cda is ubiquitously expressed in mice and humans and can inactivate dFdC into dFdU in both plasma and cells (32, 33). Notably, recent in vitro and in vivo data have provided the first evidence that high Cda expression is associated with gemcitabine resistance and a small study in pancreatic cancer patients showed that Cda ultrametabolizers were five times more likely to progress after gemcitabine-based therapy (30, 34, 35). Conversely, patients with functionally deficient Cda were associated with an increased risk of experiencing severe or even lethal adverse effects (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of acute myeloid leukemia in children with and without Down syndrome indicate that elevated CDA transcript levels correlate with poor outcome in Ara-C -based chemotherapy (29,30). CDA gene expression/activity and outcome of gemcitabine-based treatment also correlate in neuroblastoma cell lines (31) and pancreatic cancer (32). Ara-C and gemcitabine have been used in CRC treatment (33 -36), but the correlation between CDA and treatment effectiveness has not been studied.…”
Section: Discussionmentioning
confidence: 99%